Kiai's Polymorphic Leadership at Al-Muhsin Islamic Boarding School - Darvita, Puput Eci; Arif Wahyudi, Arif Wahyudib (Nursyam Center, 2024)
This study aims to provide further studies related to the leadership authority of kiai in Al-Muhsin Islamic boarding school, Pancur Village, Temayang District, Bojonegoro Regency which is still ongoing until now. This research uses power theory that emphasizes domination, knowledge, and social control. The research conducted uses qualitative methods. In collecting data, this study uses interview and observation techniques. Based on data obtained from the results of the interview. Bojonegoro has a traditional Islamic educational institution whose students live together and study under the guidance of teachers who are better known as kiai and have dormitories for students to stay, one of which is the Al-Muhsin Islamic boarding school in Pancur Village, Temayang District, Bojonegoro Regency. The leadership of the kiai at the Al-Muhsin Islamic Boarding School is authoritative and paternalistic, where the kiai has full authority in decision-making and acts as a father figure who guides students with affection but remains firm.